Czytając pisma Matki Elżbiety Czackiej (i księdza Władysława Korniłowicza) - Prussak, Maria (Colloquia Litteraria, 2022)
The author of the article tries to define the most important features of the writings of the founder of the Congregation of the Franciscan Sisters, Servants of the Cross, and on this basis define the basic assumptions of the Lasek Work, in which the community was made up of Franciscan Sisters, visually impaired people and lay people, supported by the chaplain of the Work, priest Władysław Korniłowicz. Thanks to all of them, the center in Laski was an active example of the Gospel incarnated in everyday life.